Broad-spectrum agents for flaviviral infections: dengue, Zika and beyond - Boldescu, Veaceslav; Behnam, Mira A. M.; Klein, Christian D. (Nature reviews. Drug discovery, 2017)
Infections with flaviviruses, such as dengue, West Nile virus and the recently re-emerging Zika virus, are an increasing and probably lasting global risk. This Review summarizes and comments on the opportunities for broad-spectrum agents that are active against multiple flaviviruses. Broad-spectrum activity is particularly desirable to prepare for the next flaviviral epidemic, which could emerge from as-yet unknown or neglected viruses. Potential molecular targets for broad-spectrum antiflaviviral compounds include viral proteins, such as the viral protease or polymerase, and host targets that are exploited by these viruses during entry and replication, including α-glucosidase and proteins involved in nucleoside biosynthesis. Numerous compounds with broad-spectrum antiviral activity have already been identified by target-specific or phenotypic assays. For other compounds, broad-spectrum activity can be anticipated because of their mode of action and molecular targets.